Trade Policy between Law, Diplomacy and Scholarship
XXIV, 406 p. 1 illus. in color.
Keywords: This book presents 22 topical contributions on international trade law and policy, with a particular focus on EU external trade law, addressing countries ranging from Ukraine to Switzerland and the US (TTIP), and aspects from trade and IPRs to anti-dumping. The volume constitutes a state-of-the-art treatment of the many facets of trade policy in the 21st century from legal, diplomatic and academic standpoints. The book is dedicated to the memory of Horst Günter Krenzler, former Director General for External Relations for the European Commission and Chief Negotiator for the European Union in many trade negotiations, honorary professor of European Union law at the University of Munich and an of counsel with Freshfields' Brussels office after retirement from the Commission.